Faktor dan Dampak TKW Terhadap Kondisi Sosial Ekonomi Keluarga Petani - Nailatul Khoiriyah C; Konita Mardia (Tasharruf : Journal of Islamic Economics and Business, 2021)
Poverty is a global problem, often associated with needs, difficulties and deficiencies in various living conditions, especially in the agricultural sector. The picture of material shortages which usually includes daily needs for food, clothing, housing, and health services. The problem of poverty in rural areas is more commonly found in dry land-based areas, and the symptoms of poverty are caused, among others, by the relatively less natural carrying capacity, Socio-economic infrastructure is not evenly distributed and institutions have not yet reached the local community and the quality of human resources is still relatively low. This study aims to describe: (1). What are the factors that cause peasant women to become migrant workers abroad, (2). Describe the impact of international migration of female workers (TKW, on the socio-economic conditions of the farming families left behind, while the TKW is abroad, 3) Describe the impact of international migration of female workers (TKW), on the socio-economic conditions of farming families, after TKW returns to their home area The results of this study are as follows: the study shows there are (1) factors that influence respondents to make international migration which are grouped into three parts, namely: personal factors, push factors, pull factors. The amount of remittance contributions for basic household needs. The chosen business capital is trading or opening a shop, while savings or savings are in the form of jewelry because according to them jewelry is also useful to show prestige in society.